2008
DOI: 10.4103/0019-5413.39573
|View full text |Cite
|
Sign up to set email alerts
|

Multiple intramedullary nailing of proximal phalangeal fractures of hand

Abstract: Background:Proximal phalangeal fractures are commonly encountered fractures in the hand. Majority of them are stable and can be treated by non-operative means. However, unstable fractures i.e. those with shortening, displacement, angulation, rotational deformity or segmental fractures need surgical intervention. This prospective study was undertaken to evaluate the functional outcome after surgical stabilization of these fractures with joint-sparing multiple intramedullary nailing technique.Materials and Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 24 publications
2
14
0
2
Order By: Relevance
“…We found equal percentage of basal and shaft fractures (42% each). Transverse fracture pattern (29 phalanges, 35%) was most common and was consistent with the findings in other studies 61015…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…We found equal percentage of basal and shaft fractures (42% each). Transverse fracture pattern (29 phalanges, 35%) was most common and was consistent with the findings in other studies 61015…”
Section: Discussionsupporting
confidence: 91%
“…Combination patterns have not been reported earlier. The mean patient age was comparable to that in other studies 41015. In our study, the male to female ratio was 8.7:1, while Muhammad et al 15.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…One RCT [19], one cohort study [20] and two case series [24, 26] reported on CRIF and ORIF. The outcomes per study are depicted in Table 3, and the pooled results of all studies are depicted in Table 4.…”
Section: Resultsmentioning
confidence: 99%
“…The extensor tendon over the phalangeal shaft may adhere to the fracture site during union causing stiffness of the proximal interphalangeal joint, as well as an extensor lag. 6 Early mobilization helps in preventing the adhesion. A rigid fixation is a prerequisite for early mobilization.…”
Section: Discussionmentioning
confidence: 99%